Talk Test as a practical method to estimate exercise intensity in highly trained competitive male cyclists - Gillespie, B. D.; McCormick, J. J.; Mermier, C. M.; Gibson, A. L. (The Journal of Strength and Conditioning Research, 2015)
The Talk Test (TT) has been used to determine exercise intensity among various population subgroups but not for competitive athletes. This study was designed to compare the ventilatory threshold (VT) with the last positive (+/+), equivocal (+/2), and negative (2/2) stages of the TT for highly trained cyclists. Twelve men (26.5 64.6 years, 71.96 7.6 kg) consented and completed the study, as approved by the university institutional review board. A maximal graded exercise test was used to identify VT, maximal aerobic capacity (VO2 max: 65.9 6 6.9 ml/kg/min), and maximal heart rate (HRmax: 187.3 6 11.3 b/min). On a separate visit, the TT was administered using the same protocol. Participants were asked if they could speak comfortably after a standard passage recitation. Response options were: "Yes" (+/+), "I`m not sure" (+/2), or "No" (2/2). Variables at VT were compared with the last (+/+), (+/2), and (2/2) stages of TT through t-test with Bonferroni`s adjustment (0.05/3). Differences (p # 0.017) were found between variables at VT, as compared with (+/+) TT (VO2: 32.9 6 7.7 ml/kg/min, %VO2max: 49.9 6 9.9, heart rate [HR]: 128.7 6 18.7 b/min, %HRmax: 68.6 6 7.9, rating of perceived exertion [RPE]: 11.1 6 1.1) and (+/2) TT (VO2: 44.4 6 7.5 ml/kg/min, %VO2max: 67.2 6 7.5). There were no differences between RPE- and HR-based variables at VT, as compared with (+/2) TT (RPE: 13.6 6 0.63, HR: 147.1 6 17.2 b/min, %HRmax: 78.5 6 7.4) or (2/2) TT (VO2: 48.8 6 7.8 ml/kg/min, %VO2max: 73.9 6 7.1, HR: 155.6 6 13.6 b/min, %HRmax: 83.1 6 5.3, RPE: 14.8 6 0.90). We found that when the athlete could no longer speak comfortably, he was exercising at or near his VT; we concluded that (2/2) TT estimated VT and can therefore provide a practical method to gauge exercise intensity for highly trained competitive cyclists similar to those in our study.